Rapid evolution of invasive traits facilitates the invasion of common ragweed, Ambrosia artemisiifolia. (30th May 2019) - Sun, Yan; Roderick, George K.
Abstract: Invasive alien plants, together with organisms introduced for biological control, are ideal study systems with which to address questions of whether, and how fast, organisms adapt to changing environments. We compared populations of common ragweed, Ambrosia artemisiifolia, from native (USA) and introduced (China) ranges at similar latitudes, together with herbivores introduced for biological control, to understand the rate of evolutionary adaptive response of an invasive plant to novel environments. Evolution of phenotypic traits associated with invasiveness was assessed by comparing differentiation in quantitative traits ( Q ST ) to that of neutral microsatellite genetic loci ( F ST ) and through climate data. A common‐garden experiment estimated quantitative genetic variation associated with competition with grasses and biological control history by beetles. Three growth traits (height, total and stem biomass) and plasticity associated with additional nutrients were significantly greater in invasive compared to native populations and differed from expectations from genetic drift alone. Native, but not invasive, populations exhibited traits showing evidence of past selection and correlations with climate, consistent with the recent timing of introductions. Competition experiments between invasive populations and a US bunch grass showed reduced competitive ability in populations with a history of biological control that might indicate a trade‐off between competitive ability and herbivore resistance in invasive populations. Synthesis . Our results demonstrate the rapid rate at which traits favouring invasion can evolve in invasive weeds, such as A. artemisiifolia, but also that adaptation may reflect joint effects of release from specialist herbivores and novel climatic conditions. Abstract : By comparing native and invasive common ragweed populations, our results indicated that traits of native, but not invasive populations showed evidence of past selection as evidenced through correlations with climate, which is consistent with the short time since introduction. Furthermore, invasive ragweed populations that experienced biocontrol management showed trade‐offs between competitive ability and herbivore resistance, which might be due to selection by the biocontrol agents. The figure shows regional differentiation at all quantitative traits among populations of common ragweed (QCT ) vs. at neutral genetic loci ( F CT, vertical solid lines) for the US. vs. China (left). Reduction in biomass of a grass competitor Koeleria macrantha when grown with the populations of Chinese common ragweed with different biological control history, compared to control pots (a). Overall relationship between the biomass of ragweed and that of K. macrantha in competition pots (b).